(untitled) (International Seven Journal of Multidisciplinary, 2023)
Ensuring the conservation of water reserves is a challenge for all of humanity, which makes the continuous study of new forms of treatment and use of water sources on the planet essential. One of the focuses of water conservation and sustainability is the reuse of water sources in order to guarantee the continuity of the main reserves of potable water for sedentary activities and food production. This research aimed to investigate the quality of water used for reuse at the Pinheiros subway station in the city of São Paulo (Brazil) in order to assess the degree of presence of heavy metals and other chemical elements by the X-ray fluorescence technique. by synchrotron radiation from the National Synchrotron Light Laboratory (LNLS). Data collection for a sample collected in summer and analyzed revealed a pH of 6.8 and the presence of 19 chemical elements using the technique with concentrations in the order of ng.mL-1, with emphasis on the presence of lead (Pb).